CTIM-23. A PHASE 1 TRIAL OF D2C7-IT IN COMBINATION WITH ATEZOLIZUMAB IN RECURRENT WHO GRADE IV MALIGNANT GLIOMA (MG). (9th November 2020) - Desjardins, Annick; Randazzo, Dina; Chandramohan, Vidya; Peters, Katherine; Johnson, Margaret; Landi, Daniel; Khasraw, Mustafa; Threatt, Stevie; Bullock, Chevelle; Herndon, James; Lipp, Eric; Sampson, John; et al.
Abstract: BACKGROUND: D2C7 immunotoxin (D2C7-IT) is a dual-specific recombinant immunotoxin comprising an EGFR-wt and mutant-specific (EGFRvIII) monoclonal antibody fragment and a genetically engineered form of the pseudomonas exotoxin. When injected directly into the tumor mass by convection enhanced delivery (CED), in addition to direct tumor cell killing, immunotoxins induce secondary immune responses by the activation of CD4+ and CD8+ T-cells. We completed a phase 1 dose escalation study of D2C7-IT injected by CED into recurrent WHO grade III-IV MG and identified the phase 2 dose (6, 920 ng/mL). Three patients remain in partial response more than 58, 38, and 32 months after a single D2C7-IT intratumoral infusion. As optimal induction of anti-tumor immune responses by immunotoxins is impeded by potent MG-mediated immunosuppression, we are assessing the toxicity of the combination of D2C7-IT with atezolizumab in patients with recurrent WHO grade IV MG. METHODS: Eligibility includes adult patients with recurrence of a solitary supratentorial WHO grade IV MG; ≥4 weeks after chemotherapy, bevacizumab or study drug; adequate organ function; and KPS >70%. Patient receives an intratumoral infusion of D2C7-IT and initiates two weeks later atezolizumab at 1200mg, followed by atezolizumab every 3 weeks for up to 2 years. Two cohorts of 3 patients are initially accrued to assess the toxicity of the combination. Assuming accrual continues after the initial two cohorts of 3 patients, an additional 12 patients will be accrued to the study. RESULT: The first enrolled patient experienced a grade 3 DLT (grade III ALT elevation) after the first infusion of atezolizumab, but showed a more extensive immunotherapeutic effect by imaging than observed with patients on the D2C7-IT monotherapy trial. Enrollment is ongoing. CONCLUSION: D2C7-IT monotherapy has shown prolonged survival and disease control in some patients. We are now evaluating the combination of D2C7-IT with checkpoint inhibition.